ZEP QUIZ AS AN INNOVATIVE EVALUATION MEDIA TO MEASURE THE LEARNING ACHIEVEMENT OF GRADE XI-12 STUDENTS ON NEWS TEXT MATERIALS AT SMAN 1 BANGSAL - Nur Kholida Hanum; Andri Yulia Anggraini; Istiqomah, Oktavia; Maulidinatul Ilmi; Amelia Amanda Verawati; Afredo Riski Ramadhan; Tiwi Widya Lestari; Amy Krisdiana; Sulistiyarti Wikanti Dewi (Indonesian language and literature education program Majapahit Islamic University, 2025)
This study aims to describe the use of ZEP Quiz as an innovative evaluation medium in Indonesian language learning, especially in news text material in grades XI-12 SMAN 1 Bangsal. This study uses a qualitative descriptive approach with 32 research subjects. Data was obtained through observation, evaluation, and digital documentation of learning results that were automatically recorded through the ZEP Quiz platform. The results showed that students showed high enthusiasm, actively answered questions, and were able to utilize digital features to support the learning process. The ZEP Quiz auto-recap feature provides fast, objective, and accurate information on learning outcomes. In addition, the use of ZEP Quiz creates an interactive and fun evaluation atmosphere, thereby increasing student motivation, engagement, and understanding of news text material. Thus, ZEP Quiz not only serves as an evaluation tool, but also as an active learning medium that supports the development of students' interests, motivation, and critical thinking skills in learning Indonesian in the digital era. Keywords: ZEP Quiz, learning evaluation, digital innovation, news text, learning motivation.